Plasticizer concentration effect on films and coatings based on poly(vinyl alcohol) and cationic starch blends - Petry, Jaiane Maiara; Pellá, Michelly Cristina Galdioli; Silva, Otavio Augusto; Caetano, Josiane; Dragunski, Douglas Cardoso (Food chemistry, 2024)
[Display omitted] •No significant gain comes from sorbitol percentages higher than 15%.•Amounts higher than 15% led to exudation of sorbitol on the film’s surface.•The coating increased the shelf-life of acerolas by one day at room temperature.•The coating led to a more homogeneous ripening of the fruits. Films based on poly(vinyl alcohol) (PVA) and cationic starch (CS) were combined with different percentages of sorbitol (S; 15.0, 22.5, and 30.0% w v-1) to assess the effect of plasticizer on the films. Spectroscopic analyses confirmed the interaction between them. However, micrographs indicated the formation of sorbitol crystals on the surface of the films, especially at higher sorbitol concentrations. The blends presented low water vapor transmission rate values, reaching (7.703 ± 0.000) g h−1 m−2 (PVA75CS25S15), and low solubility values for the films containing higher CS amounts. The lack of statistical differences in most parameters suggests that no significant gain comes from increasing the amount of sorbitol at percentages higher than 15%. As a coating, the blend PVA75CS25S15 successfully decreased the loss of moisture content in acerolas by 1.15 times (compared to the control), confirming the suitability of this matrix as a fruit coating.